2013
DOI: 10.1519/jsc.0b013e318260ed85
|View full text |Cite
|
Sign up to set email alerts
|

Differences and Discriminatory Power of Water Polo Game-Related Statistics in Men in International Championships and Their Relationship With the Phase of the Competition

Abstract: The aims of this study were (a) to compare water polo game-related statistics by context (winning and losing teams) and phase (preliminary, classification, and semifinal/bronze medal/gold medal), and (b) identify characteristics that discriminate performances for each phase. The game-related statistics of the 230 men's matches played in World Championships (2007, 2009, and 2011) and European Championships (2008 and 2010) were analyzed. Differences between contexts (winning or losing teams) in each phase (preli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 27 publications
4
27
0
Order By: Relevance
“…Although similar results were reported by Lupo et al (2011), who found no differences according to the match outcome, other studies (Escalante et al, 2013;Lupo et al, 2012b) have reported that winning teams perform more counterattacks than losing ones, from which it can be speculated that there is an association with competitive level. The absence of differences between winners and losers in the present study could be explained by the high level of teams analysed (elite), independent of the match outcome.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Although similar results were reported by Lupo et al (2011), who found no differences according to the match outcome, other studies (Escalante et al, 2013;Lupo et al, 2012b) have reported that winning teams perform more counterattacks than losing ones, from which it can be speculated that there is an association with competitive level. The absence of differences between winners and losers in the present study could be explained by the high level of teams analysed (elite), independent of the match outcome.…”
Section: Discussionsupporting
confidence: 84%
“…This tactic is associated with the highest rate of goal scoring (Lupo et al, 2010(Lupo et al, , 2012a(Lupo et al, ,b, 2014. In that sense, forward players should therefore train to develop their passing speed to capitalize on advantages awarded and score a goal (Escalante et al, 2013). On the other hand, it seems that winners were awarded more advantages for counterattacking actions over time, and accordingly, took fewer shots from 'other offensive arrangement' (linked to counterattacks) in 2012 than in the other tournaments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The discriminatory analysis we use to address (ii) is similar in spirit to the recent studies of Lupo et al (2012aLupo et al ( , 2014, Escalante et al (2011Escalante et al ( , 2012Escalante et al ( , 2013. However, our work differs from these investigations in that we focus specifically on tactical analysis.…”
Section: Introductionmentioning
confidence: 76%